Species cross-reactivity of rheumatoid factors and implications for immunoassays. (January 2015) - Holm, Bettina E.; Sandhu, Noreen; Tronstrøm, Julie; Lydolph, Magnus; Trier, Nicole H.; Houen, Gunnar
Abstract Rheumatoid factors (RFs) are antibodies recognizing other antibodies usually by binding to the Fc part, while heterophilic antibodies (HAbs) are antibodies reacting with immunoglobulins (Igs) from other species. In particular, RFs have been found to cause false positive results in sandwich immunoassays. In this work, we analyzed RF-positive and RF-negative sera for content of cytokines and for heterophilic reactions by enzyme-linked immunosorbent assay and bead-based sandwich immunoassays. All sera, including those with RFs, contained insignificant amounts of cytokines and chemokines, but RF-positive sera showed large false positive values for several cytokines when analyzed by fluorescent bead-based multiplex immunoassays. This non-specific binding could be minimized by reagents designed to block HAbs, i.e. by selected animal IgGs. Furthermore, sera positive for RFs reacted with several animal IgGs, when these were immobilized on beads or coated on the polystyrene surface in enzyme-linked immunosorbent assays. This reaction could be inhibited by human IgG and by agents designed to inhibit heterophilic reactions (i.e. mixtures of IgGs from different species). In conclusion, RFs and HAbs represent an identical/overlapping set of antibodies, causing false positive reactions in sandwich and other immunoassays. Such assays must be conducted in the presence of appropriate blocking agents, e.g. HBR+, and must be carefully controlled.